Analisis Risiko Paparan Karbon Monoksida (CO) Terhadap Masyarakat Sekitar Pedagang Sate Menggunakan Metode ARKL Di Kota Parepare - A.R.Amrah, Nurfardianty; Amir, Rahmi; Anggraeny, Rini; Zarkasyi, Rahmat; Nurlinda, Nurlinda (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2025)
Air pollution caused by burning activities, such as the process of grilling satay in open areas, can lead to exposure to carbon monoxide (CO) that potentially affects the health of nearby communities. This study aims to evaluate the level of risk of CO exposure experienced by the community around the Madura chicken satay vendors on Jalan Mangga, Parepare City, and to examine whether this exposure is related to respiratory complaints. The method used is a quantitative descriptive approach with Environmental Health Risk Analysis (EHRA). This research involved 126 respondents, with data obtained through the distribution of questionnaires and measurement of CO concentration using the Tropomi Explorer application. The results showed that the highest intake value reached 0.086946 mg/kg/day, while the lowest was 0.051908 mg/kg/day. The calculated Risk Quotient (RQ) remained below the risk threshold (RQ < 1), indicating that CO exposure has not posed a significant health risk. Additionally, statistical analysis results showed no significant relationship between CO exposure and respiratory disorders in the community. Factors such as short exposure time, the burning location being in open air, and good air circulation are suspected to contribute to reducing the negative impact of CO exposure.